Konsepsi Ahli Sejarah Tentang Sejarah Sosial: Review Karya Tulis Sartono Kartodirdjo, Kuntowijoyo, dan John Jean Hecth - Zulkifli Abdurrahman Usman (Lembaga Studi Agama dan Masyarakat Aceh, 2026)
This article shows that social history paved the way for History researchers to examine the sociological aspects of past societies. This thesis is based on a review of the concept of social history put forward by Sartono Kartodirdjo, Kuntowijoyo, and John Jean Hecth who affirm that social history is the study of society with a wide and diverse scope and utilizes concepts and theories in sociology. The primary data of this article is the writings of the three figures in the book Sejarah Sosial: Konseptualisasi, Model, dan Tantangannya which are analyzed using qualitative descriptive methods and subjective hermeneutic approaches. This article recommends the need for a local-based study of social history.